Using preparatory materials to facilitate fine learning and transition of postgraduate coursework students - Chih, Hui Jun; Hulcup, Claire (2016)
The increased research component in Masters by coursework degrees has meant that most contain research statistics as a core unit, and a degree of trepidation towards this is often witnessed at the beginning of semester, especially among fully online students (Chih, 2013). Students who lack confidence during this transitional period tend to withdraw from or not perform well in the unit, and so a project was undertaken to equip students enrolled in STAT6000 Health Research Methods with adequate statistical skills early in order to assist their confidence building, learning and transition. Students were asked during Orientation week to attempt a diagnostic quiz which was set at a level equivalent to completion of an undergraduate applied statistics unit. Students were then asked to attend preparatory workshops by the end of Week 2 (or to access material and workshop recordings online), which covered descriptive statistics and the normal distribution together with an introduction to inferential statistics and STATA (a statistical software program). The materials were integrated into the unit via the learning management system (Blackboard) since Orientation week. Students were later invited to evaluate the materials using an online, anonymous 11-item survey, with a Likert scale ranging from one (strongly disagree/poor) to five (strongly agree/outstanding). This was followed by open-ended questions on the most/least useful aspects of the materials and on where improvements to the material could be made. This presentation will demonstrate the effectiveness of the preparatory materials in facilitating confidence building, fine learning and transition of these postgraduate students.